Identification of Ourmiavirus 30K movement protein amino acid residues involved in symptomatology, viral movement, subcellular localization and tubule formation. (3rd April 2016) - Margaria, Paolo; Anderson, Charles T.; Turina, Massimo; Rosa, Cristina
Summary: Several plant viruses encode movement proteins (MPs) classified in the 30K superfamily. Despite a great functional diversity, alignment analysis of MP sequences belonging to the 30K superfamily revealed the presence of a central core region, including amino acids potentially critical for MP structure and functionality. We performed alanine‐scanning mutagenesis of the Ourmia melon virus (OuMV) MP, and studied the effects of amino acid substitutions on MP properties and virus infection. We identified five OuMV mutants that were impaired in systemic infection in Nicotiana benthamiana and Arabidopsis thaliana, and two mutants showing necrosis and pronounced mosaic symptoms, respectively, in N. benthamiana . Green fluorescent protein fusion constructs (GFP:MP) of movement‐defective MP alleles failed to localize in distinct foci at the cell wall, whereas a GFP fusion with wild‐type MP (GFP:MPwt) mainly co‐localized with plasmodesmata and accumulated at the periphery of epidermal cells. The movement‐defective mutants also failed to produce tubular protrusions in protoplasts isolated from infected leaves, suggesting a link between tubule formation and the ability of OuMV to move. In addition to providing data to support the importance of specific amino acids for OuMV MP functionality, we predict that these conserved residues might be critical for the correct folding and/or function of the MP of other viral species in the 30K superfamily.